Pengaruh Produksi Kelapa Sawit, Harga Minyak Kelapa Sawit Dunia, dan Emisi Karbon terhadap Volume Ekspor Minyak Kelapa Sawit Indonesia - Erwinsyah (National Research and Innovation Agency, 2024)
Indonesia is the largest producer and exporter of palm oil in the world. Unfortunately, Indonesian palm oil exports are influenced by various factors, including environmental issues, which ultimately disrupt export benefits. This research aims to analyze the influence of production, world prices, and carbon emissions on the volume of Indonesian palm oil exports. The analytical method used is Two Stage Least Square (2SLS) with simultaneous supply and demand equations for Indonesian palm oil export volumes from 1991-2021. The research results show that the increase in palm oil plantation areas in Indonesia has positively contributed to the increase in world palm oil prices as demand also increases. Furthermore, the increase in world palm oil prices has encouraged Indonesia's exports to world markets. The increase in Indonesian palm oil production has encouraged an increased volume of exports to the world market. However, market appreciation for environmentally friendly palm oil has not contributed positively to the price and increase in palm oil export volume.